On the electoral dimension of international policy coordination - Caleiro, António (2012)
The paper formalizes some of the interactions between inter-national and inter-temporal problems of policy coordination through the analysis of the implications of the synchronization (or not) of election dates on international policy cooperation. This makes it possible the determination of the gains and losses of international policy coordination and to an analysis of how the synchronization of election dates may help (electoral) international policy coordination.